Superconductivity in a misfit layered compound (SnSe)1.16(NbSe2). (7th August 2018) - Bai, Hua; Yang, Xiaohui; Liu, Yi; Zhang, Meng; Wang, Mengmeng; Li, Yupeng; Ma, Jiang; Tao, Qian; Xie, Yanwu; Cao, Guang-Han; Xu, Zhu-An
Abstract: The large size single crystals of (SnSe)1.16 (NbSe2 ) misfit layered compound were grown and superconductivity with T c of 3.4 K was first discovered in this system. Powder x-ray diffraction and high resolution transmission electron microscopy clearly display the misfit feature between SnSe and NbSe2 subsystems. The Sommerfeld coefficient γ inferred from specific-heat measurements is 16.73 mJ mol −1 K −2, slightly larger than the usual misfit compounds. The normalized specific heat jump is about 0.98, and the electron–phonon coupling constant is estimated to be 0.80. The estimated value of the in-plane upper critical magnetic field, (0), is about 7.82 T, exceeding the Pauli paramagnetic limit slightly. Both the specific-heat and H c 2 data suggest that (SnSe)1.16 (NbSe2 ) is a multi-band superconductor.